Effect of proteolysis inhibitors on serum proteinase activity and its antitryptic activity in postischemic toxemia - Protsenko, V A; Kharchenko, V Z; Veselov, V F; Spitsyn, I F; Bogadel'nikov, I V (Farmakologiia i toksikologiia, 1978)
Parenteral administration to animals of the antikallikrein serum containing 200gamma/ml of antibodies to the pancreatic kallikrein (10 ml/kg), ingitryl (1.5 Un/kg) and of tracilol (10 000 Un/kg) exerts in post-ischemic toxemia an inhibiting effect on the protamine-splitting blood serum activity and does not affect the benzoylarginine-paranitroanilide rate of splitting. Changes of the blood serum ability to bind trypsin and manifestation of the protamine-splitting activity during the first 9 hours of observation are of an undulating nature and the changes of these characteristics are reciprocal.